Deutsches Literatur-Lexikon : das 20. Jahrhundert : Biographisch-Bibliographisches Handbuch. - Kosch, Wilhelm, 1879-1960; Hagestedt, Lutz, 1960- (De Gruyter, 2013)
The Deutsches Literatur-Lexikon. Das 20. Jahrhundert is among the most comprehensive and trusted encyclopedias on German literature from the 20th and 21st centuries. The current volume features articles about Rolf Hochhuth, Carola Höhn, Walter Höllerer, and Ernst Hoferichter, among others. In keeping with its broad definition of the term literature, the lexicon also includes representatives from other specialized fields.